Greece as Central Actor Amid Geostrategic Antagonisms in the South-Eastern Mediterranean Complex - Ioannis Mazis; Sgouros, G.; Markos Troulis; Xanthippi Domatioti (The Geography of Greece - Manging Crises and Building Resilience, 2024)
We are presenting a geopolitical analysis of power redistribution in the Geopolitical Complex of the Eastern Mediterranean, as defned by the Greek-Cypriot-Turkish- Israeli-Egyptian pentagon. The factor causing the reallocation of power in the Geopolitical Complex examined isTurkey’s policy in the Eastern Mediterranean, with a focus on the illegal Turkish-Libyan Memorandum of Understanding. Therefore, this analysis covers bilateral relations and tensions between Greece and Turkey and other international poles of power (France, Italy, Germany, the USA, and Russia) and their projection in the Eastern Mediterranean. Under the aforementioned perspective, we examine the converging factors upon which this analysis is focused: (a) the debate concerning the direct or indirect projection of power in the area, (b) the opportunities for cooperation between Greece and France in the defense sector, and (c) the advantages of creating a new Southeastern Mediterranean architecture of security in the context of NATO.